Bamboo fiber polypropylene composites: Effect of fiber treatment and nano clay on mechanical and thermal properties. Issue 4 (22nd July 2014) - Rahman, Md. Rezaur; Hamdan, Sinin; Hashim, Dayang Maryani Awang; Islam, Md. Saiful; Takagi, Hitoshi
Abstract : In the current study, bamboo fibers were modified with sodium meta‐periodate in order to improve the mechanical and thermal properties of the bamboo‐clay‐polypropylene (PP) composites. Both raw and treated bamboo fibers were used in the manufacturing of the composites. The mechanical and thermal properties of the composites from modified bamboo fibers were found to increase considerably compared with those of untreated fibers. Tensile strengths of (raw bamboo fiber)/PP, (raw bamboo fiber‐clay)/PP, and (treated bamboo fiber‐clay)/PP composites showed a decreasing trend with increasing fiber loadings. However, the values for the chemically modified (bamboo fiber)‐clay‐PP composite at all mixing ratios were found to be higher than that of the original PP. The scanning electron micrographs showed that interfacial bonding between the treated fiber‐clay and matrix has significantly improved. It was determined that better dispersion of the filler into matrix occurred on 5% clay addition and fiber treatment. J. VINYL ADDIT. TECHNOL., 21:253–258, 2015. © 2014 Society of Plastics Engineers